Identification of thermoplastic starch degrading species isolated from organic food waste compost: article - Ahmad Rashidi, Arifah; Mohd Sauid, Suhaila (2017)
Thermoplastic starch is a potential alternative in solving the problem of ecological impact from the synthetic polymer. Thermoplastic starch is made of renewable sources and biodegradable. The purpose of this research is to isolate fungi that are able to degrade thermoplastic starch (TPS) from Tacca leontopetaloides and observed the fungi growth including enzyme production. In this research study, fungi species was isolated from organic food waste compost. A fungal was selected to further the study. The growth of the fungal was observed on TPS solid medium and thermoplastic starch with acetic acid (TPSAA) solid medium. Lugol’s Iodine (IKI) test was conducted to determine its capability to produce starch degrading enzyme. The weight loss was also recorded thought the study. From the research, a fungal is selected as the microorganisms for further study about degradation. According to the morphology and characteristics similarity, the fungal was identified as Aspergillus sp. It is found that the Aspergillus sp. able to grow on TPS but not on TPSAA due to the acidity of the solid medium. Besides that, Aspergillus sp. was proven as an α-amylase producer when a clearzone was appeared on the media during IKI test. The study found that the weight loss of thermoplastic starch degraded by Aspergillus sp. for 2 months is 1.81% .